Confirmatory Analysis of an Ethics Instrument for Corrections - Mei, Xiaohan (The prison journal, 2018)
In this research, we quantify the difference in correctional officers’ ethical standards, as perceived by both officers and inmates. Confirmatory factor analysis (CFA) and higher order modeling were used to validate the correctional ethics instrument. Group invariance tests at first-order level were applied to examine the invariance structure of conceptualized and operationalized ethics across staff and inmates. The evidence indicates the construct validity of the ethic instrument. Furthermore, correctional officers have a higher perception of their ethical practice than inmates on two of five common dimensions (“professional relationship with inmates” and “use of force”).